2018
DOI: 10.1186/s13104-018-3452-0
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of the free maternal health policy in rural Northern Ghana: synthesised results and lessons learnt

Abstract: ObjectiveA free maternal health policy was implemented under Ghana’s National Health Insurance Scheme to promote the use of maternal health services. Under the policy, women are entitled to free services throughout pregnancy and at childbirth. A mixed methods study involving women, providers and insurance managers was carried out in the Kassena-Nankana municipality of Ghana. It explored the affordability, availability, acceptability and quality of services. In this manuscript, we present synthesised results ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 34 publications
6
53
1
Order By: Relevance
“…The test revealed no significant difference in the cost of seeking delivery care for Wa East (Md = 35, n = 45) and that of Wa West (Md = 45, n = 82), z = −0.715, p = 0.475. This finding agrees with Dalinjong et al [10] assertion that pregnant women still purchase certain items for childbirth under the free maternal health policy in rural Northern Ghana. However, some of the respondents admitted that the cost of these items required for delivery sometimes deters them from going to the health facilities for delivery due to the high poverty levels in the study areas.…”
Section: Utilisation Of Maternal Health Servicessupporting
confidence: 92%
See 2 more Smart Citations
“…The test revealed no significant difference in the cost of seeking delivery care for Wa East (Md = 35, n = 45) and that of Wa West (Md = 45, n = 82), z = −0.715, p = 0.475. This finding agrees with Dalinjong et al [10] assertion that pregnant women still purchase certain items for childbirth under the free maternal health policy in rural Northern Ghana. However, some of the respondents admitted that the cost of these items required for delivery sometimes deters them from going to the health facilities for delivery due to the high poverty levels in the study areas.…”
Section: Utilisation Of Maternal Health Servicessupporting
confidence: 92%
“…The respondents indicated that they purchased items such as drugs, scan, and laboratory test. The results compare with the findings reported by Dalinjong et al [10] that women still paid for drugs, supplies, and laboratory services including ultrasound scans in rural northern Ghana. Access to maternal healthcare services entails the ability of women to obtain prenatal, antenatal, facility-based delivery and postnatal services [5,37].…”
Section: Utilisation Of Maternal Health Servicessupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, both NHIS enrolment and facility delivery increased significantly after the implementation of the FMH policy. This finding corroborates Dalinjong et al (2018). This is possibly due to the fact that registration with the NHIS became a condition for FMH.…”
Section: Resultsmentioning
confidence: 99%
“…Again, Ghana's NHIS is a requirement for the FMH and studies have examined the implementation and the effectiveness of the FMH (Anafi et al, 2018; Dalinjong, Wang, & Homer, 2018; Twum, Qi, Aurelie, & Xu, 2018) however, it has not been tested if NHIS enrolment has significantly increased after the introduction of the FMH. Finally, following the theory of the status quo bias , it can be argued that the use of 2008 data to assess NHIS enrolment (Mensah, Oppong, & Schmidt, 2010; Wang et al, 2017) and the FMH which were implemented in 2005 and 2008 respectively in Ghana may not tell convincing stories.…”
Section: Introductionmentioning
confidence: 99%